2021
DOI: 10.1002/jev2.12156
|View full text |Cite
|
Sign up to set email alerts
|

Label‐free characterization of an extracellular vesicle‐based therapeutic

Abstract: Interest in mesenchymal stem cell derived extracellular vesicles (MSC‐EVs) as therapeutic agents has dramatically increased over the last decade. Current approaches to the characterization and quality control of EV‐based therapeutics include particle tracking techniques, Western blotting, and advanced cytometry, but standardized methods are lacking. In this study, we established and verified quartz crystal microbalance (QCM) as highly sensitive label‐free immunosensing technique for characterizing clinically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 58 publications
0
34
0
Order By: Relevance
“…In the osteoimmunology microenvironment, MSCs are characterized by a fibroblast-like morphology that can differentiate into a variety of cell types, including osteoblastic lineage cells 30 . Subcluster 2, which was annotated as CD55 + MSCs, also expressed other classical MSC markers, NT5E 31 - 33 and LepR 34 , 35 ( Figure S3 A). We next used flow cytometry sorting to isolate CD55 + NT5E + LepR + or CD45 - CD55 + cells from human periodontal tissues of clinically healthy donors.…”
Section: Resultsmentioning
confidence: 99%
“…In the osteoimmunology microenvironment, MSCs are characterized by a fibroblast-like morphology that can differentiate into a variety of cell types, including osteoblastic lineage cells 30 . Subcluster 2, which was annotated as CD55 + MSCs, also expressed other classical MSC markers, NT5E 31 - 33 and LepR 34 , 35 ( Figure S3 A). We next used flow cytometry sorting to isolate CD55 + NT5E + LepR + or CD45 - CD55 + cells from human periodontal tissues of clinically healthy donors.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge over the active components of UC-MSC-EVs remains still partial, but the immunomodulatory effects of EVs appear to be relevant to the therapeutic impact. Adenosine signaling may contribute to the immunomodulatory activity of EVs via the conversion of AMP to adenosine by the GPI-anchored 5′-ecto-nucleotidase CD73 present on enriched UC-MSC EVs (Priglinger et al, 2021 ). A recent report by Zhai et al ( 2021 ) demonstrated that the use of EVs produced by virus-transformed hUC-MSC engineered to increase the levels of CD73 alleviated inflammation after SCI in a mouse model, and regulated macrophage polarization in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Although CD63 generally used as a surface marker to identify EVs [40], there are also reports about different miRNA cargos in CD63-positive EVs in comparison to CD47positive EVs, such as those with potentially different functions [41].…”
Section: Discussionmentioning
confidence: 99%